Software Engineering to Develop Patterns for Accumulated Values of Accounting Transactions - Sigit Widadi; Parwoto Parwoto (Universitas Muhammadiyah Yogyakarta, 2017)
Software for accounting information systems has its own peculiarities, because the transaction data is recorded in pairs over a period of time, must be traceable and can be seen again in the future at the time period desired by the user according to the accountability of financial information systems. This research presents a prototype development technique about inter-account configuration in the accounting structure and aims to provide technical assistance on how to develop a pattern of financial transaction information presentation on a double entry record system model using financial applications. Relational data set theory and concepts are used as a scientific explanation framework on how the correlation between accounts can be constructed mathematically so that the concepts can be understood by programmers when they develop software. The result of this study has been tested by applying to the financial applications in one of the microfinance institutions and it can work properly. The prototype development techniques of this research can be applied to the software development in the business field, such as services, manufacturing and trade byimplementing in the form of the software configuration system tools. furthermore, the financial application developers are expected to utilize this prototype development technique to produce more dynamic software as a financial data processor according to the accounting rules in the business organizations.